ANALISA PROTOTIPE PEMBUATAN PLTB SKALA KECIL PADA LABORATORIUM TEKNIK LISTRIK DI POLITEKNIK NEGERI PADANG - Ulfiah, Shindy Aliffianti; Rahman, Aldi; Nugroho, Satrio Dwi; Negara, Roy Bayu; Arsal, Fanji Azhary (Universitas Lampung, 2025)
A Currently, Indonesia is facing a demographic bonus, namely that the productive age is greater than the non-productive age. When entering a productive age, a person's standard of living will increase. Several studies have stated that the higher a person's standard of living, the greater their electricity needs will be. The need for electricity is currently a primary need; from waking up to resting, a person must use a lot of electricity, especially in big cities. If that happens in the future, there will definitely be more use of electricity needs. Indonesia's biggest challenge is to develop and increase a reliable and clean electricity supply. The solution is the development and application of New and Renewable Energy (EBT). The author tried to make a prototype of a Wind Power Plant (PLTB) on a small scale with tests with and without loads. The test results indicate that with a constant wind speed of 25 m/s, the results of the test without a load showed a stable voltage at 12.48 volts. When given a load of 3W, 6W, 9W, 12W, 15W, 18W, and 21W. The current value also changes with a lower light intensity.